PENGARUH RECYCLE GAME TERHADAP PENINGKATAN PENGETAHUAN ANAK KELAS 2-3 SDN 001 DESA SALO TIMUR KECAMATAN SALO - Ade Dita Puteri; Devina Yuristin (Universitas Pahlawan Tuanku Tambusai, 2023)
An increase in the amount of waste without improvement and an increase in waste processing facilities and infrastructure has created complex waste problems. Education about garbage disposal should be given to everyone possible, so that children are more concerned about the environment. The purpose of this study was to determine the effect of recycle games on increasing the knowledge of children in grades 2-3 at SDN 001 Salo Timur Village, Salo District in 2022. This type of research was a quasi-experimental design experiment with pretest and posttest approaches. The research was conducted on October 4-26 2022 with 73 respondents in grades 2-3 and a sample of 15 children in grades 2-3 at SDN 001 Desa Salo Timur using random sampling technique. Data collection used questionnaires pretest, posttest and the Recycle Game application. The data analysis used was Univariate and Bivariate analysis. The results of the study were based on pretest and posttest tests of children's knowledge before being given the recycle game treatment, most of the students had bad knowledge of 10 people (66.7%) and those who had good knowledge were 5 people (33.3%), whereas after being given the same treatment 3 people (20.0%) have poor knowledge and 12 people (80.0%) have good knowledge. Keywords: game, classification, waste, knowledge, children